2003
DOI: 10.1002/app.12844
|View full text |Cite
|
Sign up to set email alerts
|

Water absorbency of poly(sodium acrylate) superabsorbents crosslinked with modified poly(ethylene glycol)s

Abstract: A series of novel crosslinkers, polyethylene glycol diacrylate (PEGDA) with different molecular weights, were prepared, consisting of acryloyl end groups and the PEG backbones. The corresponding poly(sodium acrylate) superabsorbents of 60 mol % neutralization degree were synthesized by using ammonium persulfate and dimethylaminoethyl methacrylate as redox initiators in aqueous solution. PEGDA was characterized by FTIR and 1 H-NMR. The maximum of water absorbency (Q) of superabsorbents occurred at a specific mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…With the increment in crosslink density, the swelling capacity increases, reaches a maximum at an optimum crosslink density, and then decreases as the network becomes denser. [7][8][9]14,17,19 In the current study, on exposure to the UV radiation, the swelling capacity increased first, achieved a maximum value, and then decreased. Thus, the initial SAPs were highly crosslinked, and on exposure to UV radiation, their crosslink density decreased and reached an optimum value corresponding to maximum swelling capacity.…”
Section: Photodegradation Of Sapsmentioning
confidence: 49%
“…With the increment in crosslink density, the swelling capacity increases, reaches a maximum at an optimum crosslink density, and then decreases as the network becomes denser. [7][8][9]14,17,19 In the current study, on exposure to the UV radiation, the swelling capacity increased first, achieved a maximum value, and then decreased. Thus, the initial SAPs were highly crosslinked, and on exposure to UV radiation, their crosslink density decreased and reached an optimum value corresponding to maximum swelling capacity.…”
Section: Photodegradation Of Sapsmentioning
confidence: 49%
“…It can be attributed to higher reactivity of MBA to react with AMPS. It has been previously reported that MBA has higher reactivity than the macrocrosslinker polyethyleneglycol diacrylate (PEGDA)2, 38 in the acrylic acid polymerization. A similar reasoning can be assumed in the case of MBA and PEGDMA.…”
Section: Resultsmentioning
confidence: 99%
“…For the design of this special type of soil conditioner, a variety of different polymers have been developed and tested, which included guar [16], starch, polyacrylate and poly(ethylene glycol) [17], alginate-poly(sodium acrylate-coacrylamide) [18], alginate-g-poly(sodium acrylate)/kaolin [19], carboxymethylchitosan-g-poly(acrylic acid) copolymer [20], acrylic acid and maleic anhydride-copolymerizate [21], polyvinylalcohol-phosphate [22], acrylic acid-polyvinyl alcohol copolymer [23], polyacrylamide [24 -27], acrylamide/Nvinylpyrrolidone/3(2-hydroxyethyl carbamoyl) acrylic acid [28], poly(acrylamide-co-methyl methacrylate) [29], polyacrylamide/sodium alginate [30], polyacrylic acid [31], sodium polyacrylate, prepared by solution polymerization with N,N-methylene-bisacrylamide (bisAM) as a cross-linking agent, surface cross-linked by ethylene glycol diglycidyl ether (EGDE) [32], poly(sodium acrylate) cross-linked with modified poly(ethylene glycol) [33], sulfonated polystyrene [34], hydrolysed acrylonitrile sulfonated polystyrene [35], poly(ethylene oxide) [36], n-vinyl-2-pyrrolidone and partially neutralized acrylic acid [37], poly(tartaramide)s, poly(ester-amide)s containing oxyethylene segments [38], poly(aspartic acid) and its derivatives [39,40] poly(acrylic acid)/attapulgite/sodium humate [41].…”
mentioning
confidence: 99%